Sharing Cities for Urban Transformation: Narrative, Policy and Practice. Issue 4 (2nd October 2018) - Sharp, Darren
Abstract: Commercial sharing platforms have reshaped the transportation and housing sectors in cities and raised challenges for urban policy makers seeking to balance market disruption with community protections. Transformational sharing seeks to strengthen the urban commons to address social justice, equity and sustainability. This paper uses Transformative Social Innovation theory to develop a comparative analysis of Shareable's Sharing Cities Network and Airbnb's Home Sharing Clubs. It argues that narrative framing of the sharing economy for community empowerment and grassroots mobilisation have been used by Shareable to drive a "sharing transformation" and by Airbnb through "regulatory hacking" to influence urban policy.